Az emberi erőforrás gazdálkodás és az adókedvezmények kapcsolata - Bertalan, Péter; Potocskáné Kőrösiné, Anita (Acta Scientiarum Socialium, 2014)
Connections between human resource management and tax allowances. The legislation provides for the obligations and determines the options that may obtain the expected results during the operation of the organization, which are required of the management by the owners, and therefore the relationship of human resource management with the tax is unquestionable.In 2011 with the reform of the social security system the government started a process which radically changed the tax and social security obligations of the employers. The social security contribution has been replaced by the social contribution tax by which the payer can be entitled for tax benefits on various grounds.Based on the analysis - which was made by the National Bank of Hungary - the opportunities of tax relief are widely recognized by employers and the opportunities are exploited by them.  We made an online survey to support that analysis and to draw conclusions. The survey with 132 filling did not constitute a representative sample. The survey approached the tax reliefs from the perspective of the employees.The survey was intended not only to get a picture from the awareness of tax reliefs, but also focused on how the respondents consider the contribution of funds to increase the level of employment.Based on the results of the research were established that these tax reliefs directly affected the employers, but of course there is a positive impact - through the promotion of the job preservation and job creation - for the employees, job seekers too. However, additional measures are needed in order to the employees know the conditions of the tax reliefs, because nearly half of the responders have not heard about the support or do not know the details.
Keywords: National Bank of Hungary; HR; survey; representative sample